1993
DOI: 10.1159/000239137
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of Cephalosporins in Mice

Abstract: This study was performed in female B6C3F1 mice to confirm previously observed effects of selected cephalosporin antibiotics on nonspecific immunity, and to determine possible effects on specific acquired immunity and host resistance. Mice were treated intravenously with DQ-2556, ceftizoxime or ceftezole at 800 mg/kg/day for 3, 5, or 7 consecutive days. All three compounds increased total serum IgM levels from day 3, but had no effects on total serum IgG levels and the thymus weight. All three cephalosporin ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…Cephalosporins are a class of antibacterial agents that are active against many Gram-positive and some Gram-negative bacteria [ 1 4 ]. Beyond their antibacterial activity, cephalosporins are reported to have various immunomodulatory properties [ 1 , 2 , 5 – 8 ]. It has been found that cephalosporins reduce the secretion of cytokines and affect migration of neutrophils [ 1 , 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cephalosporins are a class of antibacterial agents that are active against many Gram-positive and some Gram-negative bacteria [ 1 4 ]. Beyond their antibacterial activity, cephalosporins are reported to have various immunomodulatory properties [ 1 , 2 , 5 – 8 ]. It has been found that cephalosporins reduce the secretion of cytokines and affect migration of neutrophils [ 1 , 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that cephalosporins reduce the secretion of cytokines and affect migration of neutrophils [ 1 , 2 , 9 , 10 ]. The influence of various cephalosporins on the humoral and cellular immune response has been also reported [ 5 – 8 , 10 ]. It has been shown, that they may inhibit mitogen-induced transformation depending on the antibiotic tested, dose and the kind of mitogen used [ 5 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ймовірною причиною збільшення відносної кількості адгезивних клітин у перитонеальному ексудаті може бути здатність бактеріальних антигенів, що входять до складу препарату «Симбітер ацидофільний», спричиняти міграцію (рекрутинг) макрофагів і/або підвищувати рівень їх адгезивної активності [12]. Застосування цефтріаксону призводило до незначного зменшення числа адгезованих клітин у перитонеальному ексудаті у порівнянні з інтактим контролем, що може бути пояснено імунотоксичною дією антибіотика [5] і/або його негативним впливом на адгезивну активність мононуклеарних фагоцитів [11]. При комбінованому застосуванні цефтріаксону та «Симбітер ацидофільний», кількість адгезованих клітин у перитонеальній порожнині була порівняною із відповідними значеннями у тварин, що отримували цефтріаксон.…”
Section: результати та їх обговоренняunclassified
“…«Симбітер ацидофільний» (SYMBITER ® ACIDOPHILUS, ТОВ «Пролі-сок», Україна) містить живі клітини пробіотичних мікроорганізмів, КУО/мл: лактобацили і лактококи -1,0×10 9 , біфідобактерії -1,0×10 8 , пропіоновокислі бактерії -3,0×10 7 , оцтовокислі бактерії -1,0×10 5 [1]. Перитонеальні макрофаги (ПМФ), що адгезують до пластику, були отримані із перитонеального ексудату згідно методики Zhang X. et al [15].…”
unclassified